PENGARUH MEDIA EDUCAPLAY TERHADAP MINAT BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN 1 DUKUH - Amaliah, Firda; Karim, Abdul; Asyiah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine how students’ learning interest develops after using the interactive learning media educaplay, as well as to assess the extent of its influence on improving learning interest in Pancasila Education. The research employed a quantitative approach with a Posttest Only Control Group Design. The sample consisted of 59 fifth-grade students at SDN 1 Dukuh, divided into an experimental class (30 students) and a control class (29 students). The instruments used were a questionnaire and an observation sheet based on four indicators of learning interest: enjoyment, attention, curiosity, and engagement. Data were analyzed using SPSS version 26 through tests of normality, homogeneity, and an independent sample t-test. The observation results indicated that students' learning interest after using educaplay fell into the “good” category. In addition, there was a significant difference between the experimental and control classes, with a significance value of 0.000 < 0.05. The average posttest score of the experimental class was 64.10, which was higher than the control class at 55.28, showing a difference of 8.82 points or a 15.96% increase. These findings indicate that the use of educaplay has a positive and significant effect on enhancing students’ learning interest in the Pancasila Education subject.